ANALYSIS OF FACTORS RELATED TO PRESENTIAL SEX BEHAVIOR IN ADOLESCENTS IN SMP 3 BOTUMOITO - Moh Arif Dulambuti; Irwan Irwan; Laksmyn Kadir (International Journal of Health Science & Medical Research, 2022)
Adolescence is a time when a person will find interesting new things. One of the problems that occur in adolescence is premarital sexual behavior. The purpose of the study was to determine the relationship between knowledge, the role of peers, sources of information (media) and the role of family/parents with premarital sex behavior in adolescents at SMP 3 Botumoito.This type of research is quantitative with a cross sectional design. The population of this research is adolescent students at SMP 3 Botumoito in 2021, totaling 71 with a sample determination using purposive sampling with 63 respondents. Data analysis using Spearman Rank correlation test.The results of the Spearman Rank correlation test for the adolescent knowledge variable, there are 26 respondents (41.1%) who have sufficient knowledge about premarital sex but have deviant premarital sex behavior as many as 14 respondents (53.8%) then the peer variable there are 38 respondents (60 ,3%) peers have an influence on premarital sex and have deviant premarital sex behavior as many as 25 respondents (65,8%) then the variable source of information (media) there are 18 respondents (28,6%) who receive a lot of information about premarital sex with deviant behavior. Then the variable of the role of family/parents there are 35 respondents (55.6%) who have a sufficient role of family/parents with less deviant behavior as many as 18 respondents (51.4%).In conclusion, there is a significant relationship between knowledge (p = 0.004), the role of peers (p = 0.020), sources of information (media) (p = 0.047) with premarital sex behavior in adolescents at SMP 3 Botumoito. There was no significant relationship between the role of family/parents with premarital sexual behavior in adolescents at SMP 3 Botumoito (p=0.939). It is suggested that the school is expected to add education about reproductive health related to adolescent sexual behavior to increase the right information for students.